Efforts to Improve Calculating Ability Through Meronce Activities at Shekinah Preschool School - Vermin Umboh; Yolan Marjuk; Ismail Marzuki (International Journal of Sustainable Applied Sciences, 2023)
This research aims to improve counting skills through bead stringing activities in 5-6-year-old children at Shekinah Waisai Early Childhood Education. The use of bead stringing as a medium engages children directly in the learning process. This study employed a collaborative classroom action research method, which involved cooperation with the class teacher in the research implementation. The research model used was the classroom action research model emphasizing the implementation process developed by Kemmis and Mc. Taggart. The subjects of this research were 12 children aged 5-6 years. Data collection methods involved the use of observation sheets (checklists), and data analysis was conducted quantitatively. The findings of this research show that color recognition skills can be improved through bead stringing activities. In the learning process, children were given the opportunity to engage in bead stringing activities using various simple and appealing bead stringing materials. The results gradually improved, as observed during the pre-action stage, reaching 61%. It further increased in the first meeting of cycle I to 61%, and increased again in the second meeting to 64%. Counting skills improved in cycle II, reaching 72% in the first meeting, and further increased to 83% in the second meeting, achieving the success target set by the researcher.